Chinese fables and folk stories - Davis, Mary Hayes; Chow-Leung (Norwood Editions : : Norwood, 1977)
A collection of Chinese folktales and fables reflecting home and school life.
Reprint of the ed. published by American Book Co., New York, in series: Eclectic readings.
Keywords: Tales -- China; Fables, Chinese